PENERAPAN MODEL KARTU BICARA (TIME TOKEN) DALAM PEMBELAJARAN BERBICARA MELAPORKAN PERISTIWA SECARA LISAN PADA SISWA KELAS IX MTs NEGERI 5 KUNINGAN TAHUN AJARAN 2019/2020 - Suryat, Suryat (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRAK: Kemampuan berbicara siswa masih minim. Salah satu faktor penyebab minimnya kemampuan berbicara siswa adalah pemanfaatan strategi mengajar. Guru masih mempunyai pemikiran lama sehingga hasil pembelajaran kurang begitu maksimal. Tujuan penelitian ini adalah untuk mendeskripsikan perencanaan model pembelajaran kartu bicara (time token), mendeskripsikan pelaksanaan kegiatan pembelajaran berbicara melaporkan peristiwa, dan mendeskripsikan peningkatan kemampuan berbicara siswa setelah menggunakan model kartu bicara (time token). Metode yang digunakan adalah metode eksperimen dengan desain pretest posttest control group design atau pretest posttest kelompok kontrol.Kata Kunci : model pembelajaran kartu bicara (time token), berbicara, berbicara melaporkan peristiwa. THE APPLICATION OF TALK CARD MODEL (TIME TOKEN) IN SPEECH LEARNING IN REPORTING EVENTS ORAL IN CLASS IX STUDENTS OF MTs NEGERI 5 KUNINGAN 2019/2020 Academic Year ABSTRACT: Students' speaking ability is still minimal. One of the factors causing the students' lack of speaking ability is the use of teaching strategies. Teachers still have old thoughts so that the learning outcomes are not optimal. The purpose of this study was to describe the planning of the talking card learning model (time token), describe the implementation of learning to speak to report events, and describe the improvement of students' speaking skills after using the talk card model (time token). The method used was an experimental method with pretest posttest control group design or pretest posttest control group.Keywords: talking card learning model (time token), speaking, speaking to report events.ABSTRACT: Students' speaking ability is still minimal. One of the factors causing the students' lack of speaking ability is the use of teaching strategies. Teachers still have old thoughts so that the learning outcomes are not optimal. The purpose of this study was to describe the planning of the talking card learning model (time token), describe the implementation of learning to speak to report events, and describe the improvement of students' speaking skills after using the talk card model (time token). The method used was an experimental method with pretest posttest control group design or pretest posttest control group.Keywords: talking card learning model (time token), speaking, speaking to report events.